Hybrid communities of practice towards developing educators’ TPACK: Implications for teacher education - Mahlo, L.; Waghid, Z.; Chigona, A. (South African Journal of Higher Education, 2024)
Although widely acknowledged for their significance, contemporary Teacher Professional Development (TPD) initiatives have faced growing criticism due to their failure to effectively foster the seamless incorporation of technology into educators’ pedagogical practices. Educators depend on their informal Communities of Practice (CoPs) rather than TPD programmes to acquire the knowledge they need to both competently and meaningfully integrate technology into their pedagogical practices. This study investigates the innovative approaches educators employ in three (n=3) Western Cape public primary schools to create a hybrid CoP in their school to improve their collective technological, pedagogical, and content knowledge (TPACK). The criticism of TPD efforts extends beyond primary and secondary school contexts. This challenge substantially impacts teacher education and highlights the increasing necessity for developing digital literacy among the professoriate in this discipline. The theoretical basis for this study was Wenger’s (1998) CoP social learning theory and Mishra and Koehler’s (2006) TPACK model. The study employed a qualitative research approach involving a cohort of 12 educators who engaged in open-ended survey questionnaires, one-on-one semi-structured interviews, and observational sessions. Additionally, the research incorporated one (n=1) school principal and two (n=2) deputy principals who actively contributed to all data collection modalities except for the survey questionnaires. Document analysis, specifically from WhatsApp group chat screenshots, was conducted across all three (n=3) schools as part of the research approach. While the data set used in this study originates from a study involving school educators, it aims to extend the findings to determine their significance for teacher education. The results revealed that the sampled educators had established an informal hybrid CoP at their respective schools through innovative approaches, such as joint enterprise, mutual engagement, and shared repertoire. These educators gained TPACK from one another throughout this process. Universities and provincial governments might profit from the findings, the knowledge gained from which could assist in their structuring of TPD programmes in ways which would foster their organic development in educators’ particular employment contexts.